Prevalência da disfunção temporomandibular, segundo o grau de ansiedade em adolescentes no município de São Roque -SP - Motta, Lara Jansiski [UNIFESP] (2011)
The aim of this study was to determine the prevalence of signs and symptoms of temporomandibulardisorder (TMD), according to the degree of anxiety in adolescents in the city of São Roque-SP and to evaluate the internal consistency and reproducibility of Fonseca’s Anamnestic Index for TMD and of the anxiety-trait part of STAI. The evaluation of signs and symptoms of TMD was obtained by the De Fonseca Questionnaire, determining the presence and severity of the disorder. The self-administered State-Trait Anxiety Inventory questionnaire (STAI) was used to assess the students’ anxiety level. The study group consisted of 3,538 adolescents aged between 10 and 19 years. To analyze the association between TMD and anxiety we used the chi-square test and for correlation between them the Spearman coefficient, adopting a significance level of 0.05. The data revealed that 73.2% (n = 2590) had some degree of TMD, where the most prevalent was the “slight” degree (50%, n = 2051). Anxiety was present in 72.7% (n = 2572). The statistical analysis showed the existence of a statistically significant association between TMD presence and anxiety with the femalestudents(p<0.001) and a statistically significant (p<0.001) positive correlation (0.401) between the degree of TMD and anxiety levels. The internal consistency of Fonseca’s questionnaire evaluated by the Cronbach alpha coefficient was 0.633, and the test value for the anxiety-trait questionnaire (STAI) was 0.700. The reproducibility of the Fonseca index questions obtained agreement between 0.519 and 0.959, while the STAI affirmations obtained concordance between 0.751 and 0.974. It was concluded that, given the internal consistency and reproducibility, the instruments can be considered reliable for a population study of TMD and trait anxiety.